2009
DOI: 10.1007/s12041-009-0024-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Dwarf mutations in grass pea (Lathyrus sativus L.): origin, morphology, inheritance and linkage studies

Abstract: Induction of mutation has been used to create additional genetic variability in grass pea (Lathyrus sativus L.). During the ongoing investigations on different induced-morphological mutants, the author detected three types of dwarf mutants in grass pea. One mutant, designated as dwf1 type was earlier identified in colchicine-induced C2 generation of grass pea variety BioR-231 while the other two, designated as dwf2 and dwf3 were isolated in 250 Gy and 300 Gy gamma ray irradiated M2 progeny of variety 'BioR-231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 17 publications
2
15
1
Order By: Relevance
“…It was observed that the progenies of tall, dwarf, bushy, prostrate and bold seeded mutants bred true for the altered traits in M 3 generation. The genes responsible for the altered plant size and growth habits were reported to be monogenic recessive [32][33][34][35][36][37]. While Konzak et al [38] and Shakoor et al [39] in wheat and triticale, respectively, reported that the polygenes are responsible for semi dwarf character in mutants; Qin et al [40] reported a dominant dwarf mutation in the single gene in rice.…”
Section: Morphological Mutation and Plant Phenotypingmentioning
confidence: 99%
“…It was observed that the progenies of tall, dwarf, bushy, prostrate and bold seeded mutants bred true for the altered traits in M 3 generation. The genes responsible for the altered plant size and growth habits were reported to be monogenic recessive [32][33][34][35][36][37]. While Konzak et al [38] and Shakoor et al [39] in wheat and triticale, respectively, reported that the polygenes are responsible for semi dwarf character in mutants; Qin et al [40] reported a dominant dwarf mutation in the single gene in rice.…”
Section: Morphological Mutation and Plant Phenotypingmentioning
confidence: 99%
“…Growth retardation is a common phenomenon orchestrated through mutagenesis, as also observed in other legumes (Talukdar, 2009;Fazal Ali et al, 2010;Kozgar et al, 2012). In lentil, similar phenomenon was observed in EMS-induced two mutant lines catLc1 and catLc2, impaired in catalase activities, but the mutants differed in magnitude of growth retardation of shoots and roots (Talukdar and Talukdar, 2013a).…”
Section: Discussionmentioning
confidence: 81%
“…This technique has been successfully used to develop cytogenetic and breeding tools in different legume crops including lentil (Fazal Ali et al, 2010;Talukdar, 2009;2013), the potential of which is now being exploited to ascertain the intrinsic metabolic events in grain legumes (Talukdar, 2012a;2012b;Tsyganov et al, 2013). Lentil is a cool-season edible pulse crop grown widely in the Indian subcontinent, West Asia, North Africa and parts of Europe, Oceania and North America (Erskine et al, 2011) and has tremendous health benefits (Erskine et al, 2011;Talukdar, 2012c).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used as an excellent cytogenetic tool along with other different stocks, developed in this crop for gene mapping and linkage group analysis (Talukdar 2008b(Talukdar , 2009a(Talukdar ,b,c, 2012a(Talukdar , 2012c, and also to reveal antioxidant defense response at aneuploid levels (Talukdar 2011c). Occurrence of trisomics in the progeny of translocation heterozygote was also reported in different legume crops (Sutton 1939;Pellew 1940;Müller 1975;Mercykutty and Kumar 1985).…”
Section: Discussionmentioning
confidence: 99%